Problem tożsamości zjawiska a konstrukcja dyrektyw praktycznych - egzemplikacja - Stańczyk, Piotr (The problem of the phenomenon identity and the construction of practical instructions - an exemplification, 2007)
The article shows connections between the way of the conceptualization of the phenomenon identity and possibilities of the formulation of practical programmes. To present the problem, the author uses examples of medical phenomena because of their clarity. The way of the identification of medical phenomena - disease units - directly influences practical programmes - methods of treatment. In order to evaluate the meaning of this problem for social sciences, the author chose the category of attitudes which is often used in many social disciplines.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 34-42